Psychological Characteristics of Athlete Ability - o‘g‘li, Bo‘riboyev Doniyor Baxtiyor; Ilhomovich, Abdullayev Akrov (European Journal of Life Safety and Stability (2660-9630), 2021)
this article focuses on improving the formation of athlete's ability, increasing the athlete's interest in the exercise process, athletes' temperament, means of forming athlete's character, the formation of skills and competencies in athletes, training of sports professionals and coaches, sports training and scientific, theoretical and methodological in the preparation for competitions, their physical and mental training, quality organization of training, the correct solution of problematic situations that arise during sports competitions, the provision of new theoretical knowledge to athletes and the rational solution of personal problems focused on developing guidelines.